Sistem Informasi E_Voting Pemilihan Ketua Osis Berbasis Web Pada SMK PUI Cikijing - Nurhadi Surojudin; Japar Sodik (Teknik Informatika, Universitas Pelita Bangsa, 2022)
This study aims to build an e-voting information system for the election of the chairman of the web-based student council at PUI Cikijing Vocational School and build an e-voting information system that can be used to present information on the results of voting results quickly and accurately and provide convenience for officers to determine the number of results. vote count. This research was conducted at SMK PUI Cikijing. The research method used to build an E-voting system is by using the prototype method, the design is carried out using UML (Unified Modeling Language) and coding the system using the PHP (Hypertext Preprocessor) programming language. The result of the research is that the Evoting system can streamline time in conducting an election for the OSIS chairman candidate at PUI Cikijing Vocational School. The steps are easy to access because almost all students can access the link provided by the officer via a computer, laptop, or handphone. Keywords: Prototype, UML, PHP, E-Voting